REPRESENTATIONS OF THE ENVIRONMENT IN CONTEMPORARY IRQI WALL PAINTINGS - Anwar Hadeeb Kareem Alamary, Dr. Munther Fadhel Hasan, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research is concerned with studying (Representations of the environment in contemporary Iraqi wall paintings), and it falls into four chapters. The first chapter is devoted to explaining the research problem, which was the answer to the following question: What is the extent of the Iraqi environment represented in contemporary Iraqi wall painting? Chapter II contains a theoretical framework consisting of two sections, the first section deals with the concept of the environment and the types and their relationship to human beings in general. The second topic includes features of the environment in contemporary Iraqi wall paintings and the experiences and methods of the most prominent contemporary Iraqi artists. Either Chapter III singled out procedures for research where the research community, including available models (samples), was chosen to sample three work murals were analyzed according to the research methodology, a descriptive and analytical approach adopted researcher in the search tool on the indicators of the theoretical framework in the sample analysis. And it includes a fourth chapter search results and models that represent t the environment of a clear sample (1, 2, 3). Also, the conclusions that showed us that the local environment has an important role in shaping the Iraqi wall painting and the diversity of its methods among Iraqi painters, and it reveals the social contents and events related to the Iraqi society, an active presence in the experiences of contemporary Iraqi painting in the sample (1, 2, 3).